2010
DOI: 10.1111/j.1754-8845.2010.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Poetry immersion: Reading, writing and performing with secondary students

Abstract: In an attempt to counter the culture of high-stakes testing and the instrumental coverage of poetry, the authors designed and taught a sustained, intensive poetry course to secondary students. In this article they advocate a deep genre study of poetry for students and teachers and highlight important principles from their work that are applicable in a variety of teaching contexts.Poetry immersion: Reading, writing, and performing with secondary students In many English classrooms, teachers are required to devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…As early as 1991 Cox argued in favour of the teaching of creative writing in British schools and emphasised that students should not only be asked to write literary essays but should also be encouraged to tackle a variety of genres, including poetry. Poetry lessons in Malta seem to be very similar to the ones in the United States as described by Schillinger, Meyer and Vinz (2010), in which poetry writing is excluded from the lesson and students are rewarded for how well they can write about poetry. In what might be considered a long‐awaited development, creative writing has finally been given some attention by being mentioned in the draft of Malta’s first National Cultural Policy, which recognises the significance of students’ right ‘to be creators of art’ (MECYS 2010: 36).…”
Section: Creative Writing and Critical Readingmentioning
confidence: 88%
See 1 more Smart Citation
“…As early as 1991 Cox argued in favour of the teaching of creative writing in British schools and emphasised that students should not only be asked to write literary essays but should also be encouraged to tackle a variety of genres, including poetry. Poetry lessons in Malta seem to be very similar to the ones in the United States as described by Schillinger, Meyer and Vinz (2010), in which poetry writing is excluded from the lesson and students are rewarded for how well they can write about poetry. In what might be considered a long‐awaited development, creative writing has finally been given some attention by being mentioned in the draft of Malta’s first National Cultural Policy, which recognises the significance of students’ right ‘to be creators of art’ (MECYS 2010: 36).…”
Section: Creative Writing and Critical Readingmentioning
confidence: 88%
“…Beach, Appleman, Hynds and Wilhelm (2006) maintain that poetry writing helps students to take on the guise of a writer and to notice the use of poetic language and techniques. Schillinger, Meyer, and Vinz (2010) and Bluett (2010) too appreciate the connection between the reading and writing of poetry and according to the latter the act of reading poetry for writing purposes ‘makes one engage with the poem in a very immediate and vital way’ (p. 46).…”
Section: Creative Writing and Critical Readingmentioning
confidence: 99%
“…Clear areas of concern can be traced through from these different sources: the impact of examinations; few opportunities for pupils to write; a dominant focus on identification of poetic technique; the prevalence of a ‘right answer’ approach. Several studies have identified such concerns and sought solutions to address them (Gordon , Wilson , Schillinger et al , Hennessy and McNamara , Xerri , Dymoke ), providing examples of innovative approaches to poetry pedagogy. This project seeks to contribute to discussions to address perceived problems in the teaching of poetry, by investigating a particular strategy to engage pupils in the reading of poetry, even given the demands of high stakes assessment.…”
Section: Contemporary Contexts For the Teaching Of Poetrymentioning
confidence: 99%
“…McGovern (1993) suggests a cognitive 'skills-approach' where the teacher should teach specific poetry reading skills explicitly over two-three years. Schillinger, Meyer, and Vinz (2010) suggest extended deep genre pedagogy where teachers co-explore poetry with students and encourage a supportive learning community. Curwood and Cowell (2011) suggest composition of multimodal poetry but say less about how one may read multimodal poetry.…”
Section: Resultsmentioning
confidence: 98%